Reviving life that has ceased on October the 7th: an attachment perspective on a virtual reality intervention - Bodner, Ehud; Mikulincer, Mario; McMahon, Elizabeth; Rizzo, Albert (Frontiers in Virtual Reality, 2024)
Unfortunately, in recent years, wars have forced many civilians to evacuate their homes and move to safe zones. The event of October 7th in many Kibbutzim near the Gaza strip exposed families who were on a Jewish holiday to the murder of family and community members. They had to leave their burned houses and move to hotels and apartment buildings in other parts of Israel. Many people, also from the Northern parts of the country, are still in new safe zones and have huge difficulties returning to their houses (and not only because of objective security reasons). In this “perspective” article, we propose a Virtual Reality (VR) application based on past and current research in attachment theory and traumatic grief. We propose that in addition to the use of exposure therapy, a VR simulation activating the attachment system can reorganize the evacuees’ figure and place attachment representations. We suggest such a simulation will revive the evacuees’ sense of safe-haven and secure base and enable them to return to their home place or adjust to a new place, thereby leading to optimal adjustment. We start with a presentation of the theory of attachment, place attachment, attachment and loss, and the two-track model of bereavement. Then, we describe the design of our VR intervention that aims to address this challenge from the attachment theory perspective with the evacuees. Finally, we discuss the challenges needing to be dealt with to implement the VR interventions through resilience centers in Israel.